Endurance and Performance of Two Different Concepts for Left Ventricular Stimulation with Bipolar Epicardial Leads in Long-Term Follow-Up - Burger, H.; Kempfert, J.; van Linden, A.; Szalay, Z.; Schoenburg, M.; Walther, T.; Ziegelhoeffer, T. (The Thoracic and Cardiovascular Surgeon, 2012)
Background Epicardial left ventricular (LV) leads represent an alternative for CRT therapy if transvenous lead implantation fails. Data on endurance, performance, the impact of the surgical approach (lateral minithoracotomy vs. median sternotomy simultaneously with other cardiac surgery), and the optimal technical concept (screw-in vs. suture-on) is limited.Methods Over a period of 48 months we evaluated 130 consecutive patients with comparable characteristics. A total of 54 screw-in (MyoDex™ 1084T, SJM) and 76 suture-on (Capture Epi 4968, Medtronic) bipolar epicardial steroid-eluting LV leads were implanted either via a left lateral or a median thoracotomy. Sensing, pacing threshold, impedance and NYHA class were recorded at defined time points.Results No surgery-related death or major complication was observed. At the time of implantation, the pacing threshold, sensing and NYHA class did not differ significantly between the two groups. The impedances of screw-in leads were significantly lower compared to those of suture-on leads. Suture-on leads showed a moderate initial drop in their pacing threshold but afterwards remained stable. Screw-in leads were characterized by a moderate but significant increase in the pacing threshold in the first year followed by a continuous decrease thereafter. Twenty-four months post-implantation no differences between both lead types could be detected. Sensing and NYHA class improved in both groups. The surgical approach had no significant impact on lead functionality.Conclusion Our study showed that the implantation of epicardial leads was safe with very low complication rates. There was no superior technical epicardial lead concept (screw-in vs. suture-on leads) and all epicardial leads demonstrated an excellent long-term performance and durability. Therefore, it seems that epicardial leads represent a good alternative to transvenous leads and surgeons should be encouraged to implant epicardial leads during concomitant cardiac surgery when the indications for CRT are present.
Keywords: pacing (incl. resynchronization/biventricular); electrophysiology (includes mapping); arrhythmia therapy (includes Maze; surgical ablation); epicardial leads; cardiac resynchronization therapy; surgical access; screw-in leads; suture-on leads